2020
DOI: 10.1101/2020.12.25.424416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell characterization of subsolid and solid lesions in the lung adenocarcinoma spectrum

Abstract: SummaryDetermining the clinical significance of CT scan-detected subsolid pulmonary nodules requires an understanding of the molecular and cellular features that may foreshadow disease progression. We studied the alterations at the transcriptome level in both immune and non-immune cells, utilizing single-cell RNA sequencing, to compare the microenvironment of subsolid, solid, and non-involved lung tissues from surgical resection specimens. This evaluation of early spectrum lung adenocarcinoma reveals a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Analysis identified that GGN cancer cells exhibited downregulation of signaling pathways related to cell proliferation and angiogenesis, distinct stromal cell transcriptomic states including reduced expression of collagens in fibroblasts, and increased activation of immune cells, relative to SADC cells. Another study interrogated, by scRNA-seq, the microenvironment of subsolid nodules (SSN) which often represent premalignancy (AAH, AIS, MIA) or early spectrum and indolent LUAD [ 84 ], and compared those to solid or uninvolved lung tissues from surgical resection lung specimens [ 95 ]. Analysis identified that both cancer-associated AT2 cells and fibroblasts contribute to the deregulation of the extracellular matrix, potentially affecting immune infiltration in subsolid lesions through ligand-receptor interactions.…”
Section: The Urgency In Premalignancymentioning
confidence: 99%
“…Analysis identified that GGN cancer cells exhibited downregulation of signaling pathways related to cell proliferation and angiogenesis, distinct stromal cell transcriptomic states including reduced expression of collagens in fibroblasts, and increased activation of immune cells, relative to SADC cells. Another study interrogated, by scRNA-seq, the microenvironment of subsolid nodules (SSN) which often represent premalignancy (AAH, AIS, MIA) or early spectrum and indolent LUAD [ 84 ], and compared those to solid or uninvolved lung tissues from surgical resection lung specimens [ 95 ]. Analysis identified that both cancer-associated AT2 cells and fibroblasts contribute to the deregulation of the extracellular matrix, potentially affecting immune infiltration in subsolid lesions through ligand-receptor interactions.…”
Section: The Urgency In Premalignancymentioning
confidence: 99%
“…In the post-TCGA era, NCI has funded a new initiative, the Human Tumor Atlas Network (HTAN), to construct three-dimensional atlases of the cellular, morphological, and molecular features of human cancers over time, including characterizations performed at singlecell resolution (Rozenblatt-Rosen et al 2020). For lung cancer, HTAN efforts have been carried out for lesions of LUAD (Krysan et al 2019), subsolid and solid lesions in the LUAD spectrum (Yanagawa et al 2020), lesions of LUSC (Teixeira et al 2019), early-stage LUAD (Sinjab et al 2021), LUAD transition to metastasis (Laughney et al 2020), and SCLC biopsies (Chan et al 2020). Outside HTAN, a few other studies have also performed scRNA-seq profiling for NSCLC tumors (Kim et al 2020;Wu et al 2021), studied the innate immune landscape in LUAD (Lavin et al 2017), and investigated therapy-induced evolution of NSCLC (Maynard et al 2020).…”
Section: Molecular and Genomic Profiling Data From Primary Tumors Pub...mentioning
confidence: 99%
“…Using concomitant analysis of tumor DNA and inferred analysis of RNASEQ data, HLA LOH and TCR clonality were increased in solid nodules compared to part-solid nodules and this was associated with increased expression of immunomodulatory genes and of CD4+, CD8+, and Treg cell infiltration. Recent work using single-cell analysis of early lung adenocarcinoma builds on these findings to show promise of more precise deconvolution of the immune landscape in these tumors and a better understanding of the ongoing biological tension between antitumor immunity and immune evasion within these nodules (16,17).…”
mentioning
confidence: 99%